Fraud Avoidance Using QR Codes on Transaction Process on Finding – Tutor Application in Android System - I Nyoman Pande Wahyu Dharmawan; R.V. Hari Ginardi (Jurnal Teknik ITS, 2017)
Finding – Tutor application is an app with Android basis. This application helps people in finding some tutors that are needed for students. In addition, Finding – Tutor also helps tutor service providers in marketing their services. This application helps the student to create a transaction order according with the students’ criteria. The tutor provider can also choose transaction according to the ability he / she can teach. However, this application should be able to handle a fraud that occurs in a condition where the tutor provider services does not come to the location of the transaction. This condition happens because if there is no feature detecting that the student and tutor service provider has met, the tutor service provider can make a false data. This kind of false data is a tutor service provider give a data to system that the tutor service provider has been in the transaction location where the real condition is different. For that occasion, Finding Tutor application require a feature to handle this fraud. To do so, Finding – Tutor uses QR Codes scanner to handle this fraud.